Lexical Variations of Coastal and Mountain Javanese in Jepara Indonesia: A Sociodialecology Study - Elly Fardzilatin; Muhammad Suryadi (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the variation of the Javanese language lexicon in the coastal and mountainous areas of Jepara Regency. This study used a qualitative approach. Data were collected by using the method of listening, speaking, interviewing and taking notes. The researcher conducted this study by listening, participating in the conversation and listening to the contents of the direct information conversation. Furthermore, the researcher used interview techniques in order to find as much data as possible. The researcher used a note-taking technique in order to record the data which had been obtained from the informant. The results of this study find 15 variations of the lexicon consisting of 5 gloss of basic vocabulary, 2 gloss of this disease and disorder, 1 gloss of livestock and animals, 3 gloss of goods and equipment, 1 gloss of this culture, said work has 2 gloss, and this adjective has 1 gloss. Phonological differences are found in the coastal and mountainous areas of Jepara